2010
DOI: 10.1007/s10495-010-0465-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics, cell death and the pathogenesis of Parkinson’s disease

Abstract: The structure and function of the mitochondrial network is regulated by mitochondrial biogenesis, fission, fusion, transport and degradation. A well-maintained balance of these processes (mitochondrial dynamics) is essential for neuronal signaling, plasticity and transmitter release. Core proteins of the mitochondrial dynamics machinery play important roles in the regulation of apoptosis, and mutations or abnormal expression of these factors are associated with inherited and age-dependent neurodegenerative dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 225 publications
(263 reference statements)
0
48
0
1
Order By: Relevance
“…24,25) Moreover, quinoproteins from dopaminequinone induced mitochondrial swelling and permeability transition of the mitochondrial membrane and reduced complex I activity and electron transport leading to dysfunction of mitochondria in human and rat brains. 12,26,27) Recent proteomics studies using radiolabeled dopamine showed that dopaminequinone covalently modified critical proteins such as mitochondrial chaperonin, ubiquinol-cytochrome c reductase, mortalin, mitofilin, creatine kinase, and NADH dehydrogenase in animal and human cells. 28,29) The covalent modification of these proteins by dopaminequinone may contribute to cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…24,25) Moreover, quinoproteins from dopaminequinone induced mitochondrial swelling and permeability transition of the mitochondrial membrane and reduced complex I activity and electron transport leading to dysfunction of mitochondria in human and rat brains. 12,26,27) Recent proteomics studies using radiolabeled dopamine showed that dopaminequinone covalently modified critical proteins such as mitochondrial chaperonin, ubiquinol-cytochrome c reductase, mortalin, mitofilin, creatine kinase, and NADH dehydrogenase in animal and human cells. 28,29) The covalent modification of these proteins by dopaminequinone may contribute to cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which PINK1 or parkin confers neuroprotection is not clear [255]. Both causes of arPD induce mitophagy or defective oxidative phosphorylation [256,257], and GTPase dynamic-related protein (Drp1) is one of the targets of Parkin [258], while PINK1 is involved in mitochondrial trafficking by forming a multiprotein complex with the GTPase Miro and the adaptive protein milton [259].…”
Section: It Improves Mitochondrial Dysfunction Altersmentioning
confidence: 99%
“…Quoi qu'il en soit, certaines différences qui semblent exister aujourd'hui entre les voies de mort mitochondriale chez ces différentes espèces pourraient aussi refléter l'état encore incomplet de nos connaissances. La drosophile est un système modèle de choix pour comprendre les maladies humaines impliquant une voie de mort mitochondriale, ou associées à une altération du fonctionnement mitochondrial [37][38][39]. La poursuite des études sur la contribution de la mitochondrie dans l'apoptose chez la drosophile pourrait bien nous révéler encore d'autres aspects de la mort cellulaire programmée impliqués dans des pathologies.…”
Section: Resultsunclassified